MAKNA KOMUNIKASI NON VERBAL DI KALANGAN GIGOLO KOTA PEKANBARU - Adhitya Putra Ruli; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Non-verbal communication is a communication process in which the message was delivered did not use words. Examples of non-verbal communication is to use gestures, body language, facial expressions and eye contact, the use of objects such as clothes, haircuts, symbols, as well as how to talk like intonation, emphasis, sound quality, style emotion and style of speaking. Dimensions of non-verbal communication that is primarily behavioral kinesic, paralinguistic, proxemics, and artifacts. The purpose of this study was to determine how the meaning of a message from kinesic behavior, paralinguistic messages, proxemic, and the meaning of the artifacts used by gigolo as a non-verbal communication to get customers / clients.This research is expected to contribute to the academic enrichment of activities that apply non-verbal communication. This research was conducted at the Social Department of Riau Province where located in the Sudirman. This study took place in December 2015 to June 2016. This study used descriptive qualitative research methods that explain and interpret the data collected and used. The data were collected by observation, interview, and documentation. The data validity checking carried out by the extension of participation and triangulation.The results of this study indicate that gigolo apply non-verbal communication profesionally, namely in terms of the behavior of kinesic, paralinguistic, proxemic message, and artifacts. In terms of behavior kinesic gigolo apply illustrator and display effect in attracting clients. All the actors created paralinguistic actions are an attempt to make prospective clients feel comfortable around him. They practice Proxemic behavior not just as a courtesy, but more than that they use as a tool to get the attention and interest of his client. While the artifacts do to stimulate in order to become more effective in communication.Keyword : Non Verbal Communication, Kinesic, Gigolo